2011
DOI: 10.1111/j.1524-4725.2010.01854.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Collagen Induction Versus Full-Concentration Trichloroacetic Acid in the Treatment of Atrophic Acne Scars

Abstract: PCI and 100% TCA CROSS were effective in the treatment of atrophic acne scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 12 publications
5
64
0
1
Order By: Relevance
“…This is similar to that observed in the study conducted by Leheta et al which also compared the two techniques among Egyptian patients. 7 In an Indian study conducted by Neerja, there was improvement with both the technique and there was no statistically significant difference in results between the two techniques. 8 But this study reported overall patient satisfaction with TCA CROSS.…”
Section: Discussionmentioning
confidence: 92%
“…This is similar to that observed in the study conducted by Leheta et al which also compared the two techniques among Egyptian patients. 7 In an Indian study conducted by Neerja, there was improvement with both the technique and there was no statistically significant difference in results between the two techniques. 8 But this study reported overall patient satisfaction with TCA CROSS.…”
Section: Discussionmentioning
confidence: 92%
“…Marked improvement ≥ 75% There was a statistically significant difference (P = 0.014) in an independent observer's after-treatment assessment between the groups according to a quartile grading scale [15] , which was used to evaluate the effectiveness of the therapies, as shown in Table 1 and In Group B, 7 patients (46.7%) ranked their improvement as marked, 5 patients (33.3%) as moderate improvement and 2 patients (13.3%) as significant and only 1 patient (6.7%) as slight improvement. There was a statistically significant difference (P = 0.038) in the patients' assessment score at the end of the treatment between the groups, as shown in Table 2 and Figure 2.…”
Section: Methodsmentioning
confidence: 90%
“…After centrifugation, the platelets and other vital growth proteins would be ready at the top of supernatant. The PRP was then drawn off, and the addition of calcium gluconate activated the PRP and resulted in the prompt release of 70% of growth factors from the α-granules within 10 minutes (and nearly all the contents within an hour).We used a quartile grading scale [15] to evaluate the effectiveness of the therapies, as stated below:…”
Section: Methodsmentioning
confidence: 99%
“…26,28 With this technique, the rolling is usually con nued un l bruising occurs, which ini ates the complex cascade of growth factors that fi nally results in collagen produc on [28][29][30] . Also it provides a clear channel for topical agents to be absorbed more eff ec vely through the top layer of skin.…”
Section: Discussionmentioning
confidence: 99%
“…30 The op mal scars to treat with skin needling are the rolling acne scars and superfi cial boxcar scars. 26,29 This technique has many advantages: 1. It is safe in all skin types and carry the lowest risk of pos nfl ammatory hyperpigmenta on when compared to laser resurfacing, chemical peels, or dermabrasion.…”
Section: Discussionmentioning
confidence: 99%